Kewarganegaraan dan Identitas - Putri, Desi Riani Dwi; Rahmawati, Noer Bunka (Jurnal PKM Manajemen Bisnis, 2025)
Citizenship and identity are two concepts that are interrelated but differ in their definition, role and influence on individuals and society. Citizenship gives a person legal status as an official member of a country, which is accompanied by legally enforceable rights and obligations. Meanwhile, identity is a more personal aspect, including factors such as culture, ethnicity, religion and language that shape an individual's identity. Citizenship and identity are two concepts that are closely related to each other in the context of modern state life. Both form an important foundation in understanding the relationship between the individual and the state and a person's position in society. The concept of citizenship not only includes legal-formal aspects, but also involves complex social, cultural and political dimensions. In the era of globalization, understanding of citizenship and identity is undergoing significant transformation. Increasing global mobility, cross-border migration, and developments in information technology have created more fluid and multilayered forms of identity. This challenges the traditional concept of citizenship which was previously limited to territorial ties and a single nationality. A more inclusive and adaptive approach is needed in understanding and managing the dynamics of citizenship and identity to create a more democratic and just society.